Identitas Gender dan Kebebasan: Kajian Feminisme Eksistensialis dalam Novel Pasung Jiwa Karya Okky Madasari - ais nur; Ester Juwinda Lase; Trisna Kumala Satya Dewi (Balai Bahasa Provinsi Riau, 2025)
Abstract This study examined the concept of gender identity through the perspective of existentialist feminism in Okky Madasari's novel entitled Pasung Jiwa. The novel depicts the struggles of the main character, a man who feels more comfortable living as a woman, against the pressures and conflicts arising from traditional societal constraints. Using a sociological approach to literature and Simone de Beauvoir's existentialist feminism theory, this research explores how individual identity and freedom are shaped and constrained by social expectations and norms. The study found that the individual's struggle to identify and express their gender identity is often commodified by social norms and reflect the tension between individual freedom and social expectations. The method used in this research is text analysis with a focus on gender dynamics and individual freedom.